Effectiveness of the Nomination Committee in Chinese Conditions - Liu, Huiyu (Transactions on Economics, Business and Management Research, 2024)
The nomination committee is given high hopes of protecting the independence of independent directors, but the repeated news about the incompetent independent directors makes us question the effectiveness of the nomination committee system. Lacking of mandatory constraints of relevant laws and regulation, the nomination committee system is not carried out ideally in China. Hence, we wonder whether the nomination committee could function effectively in China and how to improve it to adapt to Chinese conditions. Herein, we examines the effectiveness of nomination committees and the factors that influence the operation of nominating committees.